The Relationship Between the Intensity of the Use of the Tiktok Application and the Mental Health of Nursing Students - Anisah Syofiah SL; Ari Rahmat Aziz; Nurul Huda (CV. Rayyan Dwi Bharata, 2023)
The mental health of nursing students tends to be disrupted due to academic pressure, time demands and large clinical responsibilities, this causes nursing students to need coping strategies to prevent or overcome mental disorders. The study aims to determine the relationship between the intensity of using the TikTok application and the mental health of nursing students. This study used a descriptive design with a cross sectional approach. The research sample was 249 nursing students who were taken based on inclusion criteria using purposive sampling technique. The data collection tool used was a questionnaire and the analysis used was bivariate analysis using the chi square test. The highest intensity of using the TikTok application is in the moderate category with 113 (45.4%) and 123 respondents indicating mental health (49.4%). The statistical test results showed that there was a significant relationship between the intensity of using the TikTok application and mental health (p value 0.001) alpha (0.05). The intensity of using the TikTok application with mental health has a significant relationship.